1988
DOI: 10.1073/pnas.85.1.252
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus suppresses expression of human beta-interferon.

Abstract: To determine whether hepatitis B virus (HBV) regulates the expression of the human fl-interferon gene, a series of recombinant bovine papilloma virus plasmids containing the human interferon gene and various fragments of the HBV genome were constructed and used to transform C127 cells, a murine fibroblast line. Analysis of the DNA from transformed C127 cells indicated that the interferon gene was intact and that the plasmids replicated as stable multicopy elements. The 1828-base-pair BamHI HBV DNA fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…7 and 8). In such infections, the concentration of circulating IFN-a is reduced compared to patients with acute infection (9), suggesting that one strategem used by HBV to circumvent the effects of IFN may be to inhibit its production (10). Attempts to overcome this deficiency by treating patients with exogenous IFN-a have met with considerable success, but many treated patients are not cured (11).…”
mentioning
confidence: 99%
“…7 and 8). In such infections, the concentration of circulating IFN-a is reduced compared to patients with acute infection (9), suggesting that one strategem used by HBV to circumvent the effects of IFN may be to inhibit its production (10). Attempts to overcome this deficiency by treating patients with exogenous IFN-a have met with considerable success, but many treated patients are not cured (11).…”
mentioning
confidence: 99%
“…Moreover, HBV has been shown to suppress the expression of the human IFN-P gene [72,73] and to induce a cellular resistance to the action of IFNs [74], These inhibitory effects against the action of IFN might be abolished, too. Unfortunately, a first trial has not shown any beneficial effect of combination therapy in 9 patients [75].…”
Section: Combination Of Lamivudine With Ifnmentioning
confidence: 99%
“…Specifically, the simian virus 40 early promoter enhancer, 69 108 and several HBV promoters (C, S1, S2, X) have been shown to be targets of HBx 67,68,88-91,103,106-108,112-115 as have cellular genes such as c-fos, c-myc, beta interferon, IL-6, iNOS, albumin, MHC antigenes, and beta actin. 91,103,108,[116][117][118][119][120][121][122] Isolated synthetic consensus transcription factor binding sites for AP1, AP2, AP3, NFκB, and SP1 can be activated, suggesting that they may be natural targets for transactivation. 65,114,116,123,124 The wide range of targets suggests that the transactivating function is of general importance.…”
Section: Transactivation By the Hbx Proteinmentioning
confidence: 99%